A nice result.

Given that \(\quad a+b+c=0\)

Prove that : \[2(a^4+b^4+c^4)=(a^2+b^2+c^2)^2\]

Nice proofs are always welcome!

Note by Nihar Mahajan
3 years, 9 months ago

No vote yet
1 vote

  Easy Math Editor

MarkdownAppears as
*italics* or _italics_ italics
**bold** or __bold__ bold

- bulleted
- list

  • bulleted
  • list

1. numbered
2. list

  1. numbered
  2. list
Note: you must add a full line of space before and after lists for them to show up correctly
paragraph 1

paragraph 2

paragraph 1

paragraph 2

[example link](https://brilliant.org)example link
> This is a quote
This is a quote
    # I indented these lines
    # 4 spaces, and now they show
    # up as a code block.

    print "hello world"
# I indented these lines
# 4 spaces, and now they show
# up as a code block.

print "hello world"
MathAppears as
Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.
2 \times 3 \( 2 \times 3 \)
2^{34} \( 2^{34} \)
a_{i-1} \( a_{i-1} \)
\frac{2}{3} \( \frac{2}{3} \)
\sqrt{2} \( \sqrt{2} \)
\sum_{i=1}^3 \( \sum_{i=1}^3 \)
\sin \theta \( \sin \theta \)
\boxed{123} \( \boxed{123} \)

Comments

Sort by:

Top Newest

Lets start off by finding the value of \(\ a^2 +b^2 +c^2 \) in terms of another sum by doing the following: \[(a+b+c)^2 = a^2 +b^2 +c^2 +2(ab +ac +bc) = 0 \Rightarrow\ (a^2 +b^2 +c^2)^2 = 4(ab+ac+bc)^2 \]

Now expanding out the RHS: \[... = 4(a^2 b^2 +a^2 c^2 + b^2 c^2 +2abc(a+b+c)) = 4(a^2 b^2 +a^2 c^2 + b^2 c^2) \]

Now if we expand out \(\ (a^2 +b^2 +c^2)^2 \) and cancel out terms we get: \[ a^4 +b^4 +c^4 = 2 (a^2 b^2 +a^2 c^2 + b^2 c^2) \ ........ \ (1) \] \[\Rightarrow\ 2(a^4 +b^4 +c^4) = a^4 +b^4 +c^4 + 2 (a^2 b^2 +a^2 c^2 + b^2 c^2) \]

\[\therefore\ 2(a^4 +b^4 +c^4) = (a^2 +b^2 +c^2)^2 \]

Curtis Clement - 3 years, 9 months ago

Log in to reply

Yeah! Thanks , I got an easier way . Read below.

Nihar Mahajan - 3 years, 9 months ago

Log in to reply

Approach: Factoring polynomials using the (slightly abused) remainder factor theorem for polynomials in several degrees.

Define \( f(a, b, c) = 2 (a^4 + b^4 + c^4) - (a^2 + b^2 + c^2) ^2 \).
We want to show that if \( a+b+ c = 0 \), then \( f(a, b, c) = 0 \). This strongly suggests to us that \( f(a, b, c) = (a+b+c) \times g(a, b, c) \).

If \( a + b + c = 0 \), then we have \( f( -b-c, b, c ) = 0 \). Notice that the powers of \(a \) only occur in even degree, hence \( f(a, b, c) = f(-a, b, c) \). This implies that \( f( b+c, b, c ) = 0 \), and thus that \( a-b-c \mid f(a, b, c) \). Cyclically, we also get that \( b-c-a \mid f(a,b,c)\) and \( c-a-b \mid f(a,b,c) \).

Putting this all together, this strongly suggests that

\[ (a+b+c)(a-b-c)(b-c-a)(c-a-b) \mid f(a,b,c) \]

Since both sides have the same degree (4), we know that they differ by a constant. In fact, we can now verify that

\[ f(a, b, c) = - (a+b+c)(a-b-c)(b-c-a)(c-a-b) \]

Calvin Lin Staff - 3 years, 9 months ago

Log in to reply

The equation \(2(a^4 + b^4 + c^4) = (a^2 + b^2 + c^2)^2\) is equivalent to \[-a^4 - b^4 - c^4 + 2a^2 b^2 + 2a^2 c^2 + 2b^2 c^2 = 0.\] This equation factors as \[(a + b + c)(-a + b + c)(a - b + c)(a + b - c) = 0,\] and the result follows.

This factorization comes up in Heron's formula: \[ \begin{align*} K^2 &= s(s - a)(s - b)(s - c) \\ &= \frac{1}{16} (a + b + c)(-a + b + c)(a - b + c)(a + b - c) \\ &= \frac{1}{16} (-a^4 - b^4 - c^4 + 2a^2 b^2 + 2a^2 c^2 + 2b^2 c^2). \end{align*} \]

Jon Haussmann - 3 years, 9 months ago

Log in to reply

Great! That's the "Use Heron's Formula" that I alluded to. There are many ways to write the expression of \(K\), and most people are only familiar with the factored form, instead of the expanded form.

Calvin Lin Staff - 3 years, 9 months ago

Log in to reply

Really great , I was curious of a heron's formula solution. Thanks!

Nihar Mahajan - 3 years, 9 months ago

Log in to reply

Use the convention of \(S_1 = a+b+c\), \(S_2=ab+bc+ca\) and \(S_3 = abc\), and \(P_n = a^n+b^n+c^n\). Then by Newton's Sum method:

\(P_2 = S_1 P_1 - 2S_2 = 0 - 2S_2 = -2S_2\)

\(S_4 = S_1P_3-S_2P_2+S_3P_1 = 0 -S_2(-2S_2) + 0 = 2S_2^2\)

Now \(LHS = 2P_4 = 4S_2^2\) and \(RHS = P_2^2 = (-2S_2)^2 = 4S_2^2 = LHS\)

Chew-Seong Cheong - 3 years, 9 months ago

Log in to reply

Plug In 1+1-2 xD xD Just kidding. I'm on it!

Mehul Arora - 3 years, 9 months ago

Log in to reply

That's the most special case. -_-

Nihar Mahajan - 3 years, 9 months ago

Log in to reply

×

Problem Loading...

Note Loading...

Set Loading...